Current Concepts and Management Approaches in Nonalcoholic Fatty Liver Disease - Bashar M. Attar; David H. Van Thiel (The Scientific World Journal)
Nonalcoholic fatty liver disease (NAFLD) is the most common cause of liver dysfunction worldwide. NAFLD may progress to nonalcoholic steatohepatitis (NASH) and in turn cirrhosis. Importantly, hepatic cancer can occur in NASH in the absence of cirrhosis. The cardinal histologic feature of NAFLD is the presence of an excessive accumulation of triacylglycerols and diacylglycerols in hepatocytes. The presence of obesity and insulin resistance lead to an increased hepatic-free fatty acid (FFA) flux creating an environment appropriate for the development of NAFLD. The generation of toxic reactive oxygen species with the production of hepatic injury and inflammation as a consequence of FFA oxidation will ultimately lead to the initiation and progression of fibrosis. Lifestyle modifications specifically weight loss, physical exercise, and cognitive behavior therapy have been recommended as treatments for NASH. Dietary fructose is an independent risk factor for the development of NAFLD. Pioglitazone can be used to treat biopsy-proven NASH; however, its safety risks should be considered carefully. Greater consumption for coffee, independent of its caffeine component, has been associated with a significant reduced risk of advanced fibrosis in NASH. Additional data are needed before recommending bariatric surgery as an established option for the specific treatment of NASH.